2019
DOI: 10.16965/ijar.2018.427
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Staheli Arch Index in Tribal Children of Jharkhand State

Abstract: Pes planus and pes cavus are the two common foot conditions, which fascinate the attention of researchers. A deviation from normal foot arch structure is associated with unstable gait. This study aims at assessing the staheli arch index (SAI) of Jharkhand tribal children. This study was carried out on children belonging to various tribal groups of Ranchi and Angara districts of Jharkhand. Graphical footprints of the study subjects were recorded and assessed using SPSS-16. The mean right SAI was 0.63 and 0.61 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…More forefoot plantar pressure which is seen in the obese foot may hinder obese children in the performance of physical activity. Shanmukha V V et al, 11 in 2019 studied Staheli Arch Index in the Tribal children of Jharkhand State. Cross sectional study performed on 360 male and female children of less than 15 years age.…”
Section: Discussionmentioning
confidence: 99%
“…More forefoot plantar pressure which is seen in the obese foot may hinder obese children in the performance of physical activity. Shanmukha V V et al, 11 in 2019 studied Staheli Arch Index in the Tribal children of Jharkhand State. Cross sectional study performed on 360 male and female children of less than 15 years age.…”
Section: Discussionmentioning
confidence: 99%
“…This result was similar to studies done by Okezu OC et al, Aenumulapalli A et al 11 However, the results were different in a study Vangara SV et al who found that males have a greater risk of pes planus than women with a prevalence of 42% in men and 36% in women. 19 Many authors found that men displayed significantly flatter feet than the women. However, in the present study, there was more prevalence of pes planus among female on both feet compared to male.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil penelitian mengenai pengaruh pengalaman auditor terhadap kualitas audit pernah dilakukan oleh (Turgarini, 2018), (Saputra, Adha, Ariyanti, & Gunawan, 2019), (Vangara, Kumar, Gopichand, & Puri, 2019), (Agustina et al, 2019) membuktikan bahwa pengalaman berpengaruh terhadap kualitas audit. Berbeda dengan hasil penelitian (Septiana, Munthe, Fatimah, & Latifah, 2019), (Yohana Ariska Sihombing & Triyanto, 2019) yang membuktikan bahwa pengalaman tidak berpengaruh terhadap kualitas audit.…”
Section: Pendahuluanunclassified
“…Hasil penelitian mengenai pengaruh independensi auditor terhadap kualitas audit yang pernah dilakukan oleh (Oktaviani, 2016), (Siahaan & Simanjuntak, 2019), (Palupi, Suratno, & Amilin, 2018), (Gunur, Makur, & Ramda, 2018), (Vangara et al, 2019), (Yuniar, 2019), (Laksita & Sukirno, 2019), membuktikan bahwa independensi berpengaruh positif dan signifikan terhadap kualitas audit. Berbeda dengan hasil penelitian (Mulyani & Munthe, 2018), Suharti & Apriyanti (2019) yang membuktikan bahwa independensi tidak berpengaruh terhadap kualitas audit.…”
Section: Pendahuluanunclassified